Effect of modified atmosphere packaging combined with plant essential oils on preservation of fresh-cut lily bulbs. (1st June 2022) - Jiang, Fenghua; Zhou, Lei; Zhou, Wei; Zhong, Zhiwei; Yu, Kaibo; Xu, Jing; Zou, Liqiang; Liu, Wei
Abstract: Fresh-cut lily bulbs have broad consumption prospects in the vegetable market due to their high nutritional value and convenience in processing; however, potential discoloration and microbial infection during storage adversely affect their quality. This study investigated the effect of modified atmosphere packaging (MAP) and plant essential oils (EOs) on the preservation of lily bulbs. The results showed that MAP significantly preserved the color and weight of lily bulbs, and different MAP conditions caused different effects on bacterial inhibition. Low oxygen-MAP (L-MAP) showed a stronger antibacterial effect than air-MAP (A-MAP), whereas appropriate antibacterial agents were still needed to improve the antibacterial effect. Therefore, plant EOs were employed to further control the growth of microorganisms by preparing plant EO solid particles (PESP). The combined use of L-MAP and PESP significantly prolonged the shelf life of lily bulbs to 12 d with higher contents of nutrients and better appearance quality compared to the control. Furthermore, the physiological metabolism of lily bulbs was regulated by combined treatment with L-MAP and PESP, which inhibited starch degradation, MDA accumulation and respiratory oxidase activities. Highlights: MAP efficiently preserved the color and weight loss of fresh-cut lily bulbs. Plant EOs were solidified and slowly released with strong antibacterial effects. Combination of MAP and plant EOs extended the shelf life of lily bulbs to 12 days. Respiratory and reactive oxygen metabolism were regulated by MAP and plant EOs.